A multi-component theory-based behaviour change intervention to increase HIV self–testing uptake and linkage to HIV prevention, care and treatment among hard to reach adults in Northern Tanzania - Njau, Bernard Joseph (Department of Public Health and Family Medicine, 2021)
To achieve the WHO targets of 95–95–95 by 2030, whereby 95% of all people living with HIV (PLHIV) know their status, 95 % of all people with an HIV diagnosis receive sustained antiretroviral therapy (ART), and 95 % of all people receiving ART achieve viral suppression, it is imperative to introduce novel community–based testing approaches such as HIV self-testing (HIVST). HIV self–testing has been shown to empower non– testers in both developed and underdeveloped countries, to be aware of their HIV status. However, no studies on the uptake of HIVST have been conducted on hard to reach populations in Northern Tanzania. The hard to reach populations for this thesis were female bar workers (FBWs) and mountain climbing porters (MCPS) in Northern Tanzania, who exhibit high-risk behaviours for HIV infection and low rates of HIV testing and / or repeat testing. It is important to find ways to increase the uptake of HIV testing in these populations and HIVST is proposed as a means of improving HIV testing coverage in hard-to-reach populations in the context of a long-standing HIV testing program. Existing implementation science literature suggests that behaviour change interventions (BCIs) guided by behaviour change theories and using planning and evaluation frameworks (i.e. PRECEDE-PROCEED model) can be effective in increasing HIV-related behaviour change. However, the current evidence on the effectiveness of HIV-related BCI is from studies conducted in high-income countries. To address the low HIV testing rates and/or repeat testing, it was important to undertake a project of research to develop and evaluate a theory-based behaviour change intervention (BCI) to increase HIVST uptake and linkage to HIV prevention, care and treatment among FBWs and MCPs in Northern Tanzania. This thesis aimed to develop and evaluate a multi-component theory-based BCI to increase HVST uptake and linkage to HIV prevention, care and treatment among female bar workers and mountain climbing porters in Northern Tanzania.